Peran Penyelenggara Pemilu dalam Pemilihan Legislatif 2014 di Kabupaten Sidoarjo - Dwi Purnamasari; Ashabul Kahfi; Arief Fatchur Rachman (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aims to analyze and determine the role of the Election Supervisory Committee and the Commission (general election commission) Implementation of legislative elections in 2014 in Sidoarjo and analyze the factors that cause a lack of understanding of policy formulation election organizers in the respective organizers of the Role of Election Supervisory Committee and the General Election Commission. This research method is using descriptive qualitative approach. The data needed is a secondary data in the form of books, journals, articles, print media (newspapers) and the mass media as well as primary data obtained from informants through. Based on the results of this study concluded that the role of each institution in the administration of elections has not run optimally in accordance with Law Number 15 of 2011 on the Election. In the implementation on the ground found some constraints on each institution in organizing legislative elections in 2014 related to the duties and responsibilities between the Role of the Election Supervisory Committee and the General Election Commission.